2016
DOI: 10.1002/mrm.26400
|View full text |Cite
|
Sign up to set email alerts
|

Application of dual19F and iron cellular MRI agents to track the infiltration of immune cells to the site of a rejected stem cell transplant

Abstract: A dual-labeling technique was used to noninvasively track two distinct cell populations simultaneously. This information could be used to provide additional insight into the cause of graft failure. Magn Reson Med 78:713-720, 2017. © 2016 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Specificity and quantitation issues can be overcome by use of fluorinated cellular labeling agents (29,(65)(66)(67)(68). Previous studies have used fluorine cell labeling for several different cell types administered as an external cellbased therapy (i.e., dendritic cells (31,65), stem cells (67)), or to label macrophages to study inflammation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Specificity and quantitation issues can be overcome by use of fluorinated cellular labeling agents (29,(65)(66)(67)(68). Previous studies have used fluorine cell labeling for several different cell types administered as an external cellbased therapy (i.e., dendritic cells (31,65), stem cells (67)), or to label macrophages to study inflammation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although PET and SPECT use radiotracers, the two technologies are significantly different [9,[12][13][14]17]. There are several positron-emitting nuclei used in the clinic for PET imaging that vary in decay half-life from minutes ( 15 O and 13 N) to 1-2 h ( 18 F and 68 Ga) to nearly 13 h ( 64 Cu), with 18 F being the most commonly used tracer. The importance of half-life in direct SC labeling is that it limits the temporal window to label, administer and track cells as they home and accumulate in their target tissue.…”
Section: Advantages and Challenges Of Sc Imaging Methods Radionuclidementioning
confidence: 99%
“…19 F resides in cancellous bone in living systems and is not detectable in vivo. Unfortunately, despite the absence of background signal, 19 F signal is low requiring much higher concentrations than hydrogen-based contrast agents for detection [67,68]. The highest concentration of exogenous 19 F is provided by PFCs that are typically composed of carbon and fluorine atoms that are immiscible in water and must be administered as emulsions [69,70].…”
Section: Mrimentioning
confidence: 99%
“…Several studies have confirmed that 19 F MRI could be an appropriated method to track macrophages in a large scale of diseases such as arthritis [109], cancer [110], [111], pulmonary inflammation [112], cardiovascular inflammation [113], [114] or transplantation rejection [115]- [117].…”
Section: Cell Trackingmentioning
confidence: 99%